A supported perovskite catalyst, its preparation method and use
By optimizing the Pt loading and preparation method, a supported Pt/CeCuO3 catalyst was prepared, which solved the problems of insufficient photothermal performance of CeCuO3 catalyst and poor dispersibility of Pt/CeCuO3 catalyst. This resulted in highly efficient photothermal synergistic catalytic methanol reforming for hydrogen production, with significantly improved catalyst structural stability and activity.
Patent Information
- Application Number
- CN202611255765.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-11-03
AI Technical Summary
Existing CeCuO3 perovskite catalysts have narrow light absorption range, low photothermal conversion efficiency, insufficient active sites, and poor catalytic activity and stability. Existing Pt/CeCuO3 catalysts have unreasonable Pt loading, poor nanoparticle dispersion, and poor photothermal synergistic catalytic effect.
By optimizing the Pt loading to 1%~5%, Pt nanoparticles were loaded onto the surface of CeCuO3 support using an impregnation method. Combined with citric acid as a solvent and calcination treatment, uniformly dispersed Pt nanoparticles were formed, enhancing the synergistic effect with the CeCuO3 support, broadening the light absorption range, and improving the photothermal conversion efficiency.
At 130℃ and 130 mW·cm-2, the methanol conversion rate reached its peak. The catalyst structure was stable and exhibited excellent resistance to carbon deposition and agglomeration. After 150 hours of continuous reaction, the activity decayed by only 1.7%, and its stability was far superior to that of pure support and other comparative catalysts.
Smart Images

Figure CN123024533A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy catalytic materials and photothermal catalytic hydrogen production technology, specifically relating to a Pt-supported perovskite CeCuO3 catalyst, which is suitable for photothermal synergistic catalytic methanol steam reforming to produce hydrogen. Background Technology
[0002] With the escalating energy crisis and the advancement of dual-carbon goals, the development of clean energy has become crucial for energy transition. As a clean and efficient secondary energy source, the core bottleneck for the large-scale application of hydrogen energy lies in low-cost, high-efficiency hydrogen production technology. Among existing hydrogen production technologies, water electrolysis is energy-intensive and costly, fossil fuel reforming results in high carbon emissions, and biomass hydrogen production is limited by raw material constraints, making large-scale application difficult. Methanol reforming, on the other hand, offers a wide range of raw materials, a mild reaction process, and convenient storage and transportation, making it a highly promising hydrogen production technology that can effectively solve the challenges of hydrogen storage and transportation.
[0003] Methanol steam reforming is currently the most widely used methanol reforming hydrogen production process. However, it is a strongly endothermic reaction, and traditional thermocatalysis requires a large amount of external energy, resulting in low energy efficiency and easy catalyst deactivation. Photothermal catalysis technology can utilize solar energy to achieve synergistic effects of light and heat energy, effectively solving the above problems and representing an important development direction for methanol reforming hydrogen production. The core of photothermal catalytic methanol reforming hydrogen production is the catalyst, which needs to possess good light absorption, thermal stability, and catalytic activity. Among existing catalysts, noble metal catalysts have high activity but are expensive and prone to aggregation, transition metal oxides are inexpensive but lack sufficient activity, while perovskite oxides have stable structures and tunable active sites, making them ideal catalyst supports.
[0004] In perovskite oxides, Ce provides oxygen vacancies and Cu exhibits certain catalytic activity, making them widely used in catalysis due to their low cost. However, CeCuO3 alone has a narrow light absorption range and insufficient active sites, resulting in poor photothermal conversion efficiency and catalytic stability, which is insufficient to meet the requirements of photothermal catalytic hydrogen production. Modification with noble metals can improve the performance of CeCuO3. Pt catalysts, with their good electronic conductivity and strong photothermal conversion ability, can effectively activate methanol molecules, inhibit carbon deposition, and improve catalyst stability, making them a commonly used modified noble metal. However, existing CeCuO3-supported Pt catalysts still have significant shortcomings: firstly, the Pt loading is not properly optimized; both excessively high and low loading can affect catalytic performance and increase costs; secondly, the poor dispersion of Pt nanoparticles leads to weak synergistic effects with the support, resulting in poor photothermal catalytic performance; and thirdly, the optimized design for photothermal catalytic methanol reforming to hydrogen production is insufficient, making it difficult to achieve efficient and stable methanol conversion.
[0005] Therefore, in view of the shortcomings of existing single CeCuO3 perovskite catalysts, such as poor photothermal performance and insufficient catalytic activity, as well as the unreasonable Pt loading, poor dispersion, and poor photothermal synergistic catalytic effect of existing supported Pt / CeCuO3 catalysts, developing a supported Pt / CeCuO3 perovskite catalyst that is suitable for photothermal catalytic methanol reforming to hydrogen production, has optimized Pt loading, and has excellent performance has become a technical problem to be solved by those skilled in the art. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies by providing a supported perovskite catalyst for photothermal catalytic methanol reforming to produce hydrogen. It solves the problems of narrow light absorption range, low photothermal conversion efficiency, insufficient active sites, and poor catalytic activity and stability of single CeCuO3 perovskite catalysts. At the same time, it overcomes the defects of existing Pt / CeCuO3 catalysts, such as unreasonable Pt loading, poor nanoparticle dispersion, weak synergistic effect with the support, and poor photothermal catalytic effect.
[0007] To achieve the above objectives, the present invention provides a supported perovskite catalyst comprising a perovskite CeCuO3 support and Pt nanoparticles supported thereon, wherein the Pt loading is 1% to 5% based on the mass of the CeCuO3 support.
[0008] Furthermore, the load of Pt is 3%.
[0009] The present invention also provides a method for preparing the above-described supported perovskite catalyst, comprising the following steps: (1) Weigh out the cerium source and copper source according to the stoichiometric ratio of CeCuO3, dissolve them in deionized water, and stir until completely dissolved; (2) Add citric acid as a complexing agent and stir to dissolve; (3) Heat in a water bath, stir to form a sol, and then age to obtain a gel; (4) Dry the gel to obtain a dry gel; (5) Grind and calcine the dry gel to obtain CeCuO3 perovskite carrier powder; (6) Weigh the Pt precursor according to the target Pt loading, prepare a solution, load the Pt precursor onto the surface of CeCuO3 support by impregnation method, and then dry it; (7) The Pt precursor is reduced to Pt nanoparticles by secondary calcination under a reducing atmosphere, and then cooled and ground to obtain the supported Pt / CeCuO3 catalyst.
[0010] Furthermore, in step (1), the cerium source is cerium nitrate hydrate, and the copper source is copper nitrate hydrate, with a molar ratio of 1:1.
[0011] Furthermore, in step (2), the molar ratio of citric acid to total metal ions is 1.3 to 1.6:1, preferably 1.5:1.
[0012] Furthermore, in step (3), the water bath temperature is 60~70℃, the gelation time is 2~3h, and the aging time is 12~24h.
[0013] Furthermore, in step (5), the calcination heating rate is 2~5℃ / min, the calcination temperature is 550~650℃, and the calcination time is 3~6h.
[0014] Furthermore, in step (7), the secondary roasting heating rate is 1~3℃ / min, the roasting temperature is 350~450℃, and the roasting time is 2~3h; the reducing atmosphere is an argon-hydrogen mixture.
[0015] The present invention also provides the application of the supported perovskite catalyst as described above or the supported perovskite catalyst prepared by the above method in the photothermal catalytic methanol steam reforming hydrogen production reaction.
[0016] Furthermore, the conditions for the photothermal catalytic methanol steam reforming to produce hydrogen are: reaction temperature 130℃, light intensity 130 mW·cm. -2 .
[0017] The beneficial effects of this invention are: This invention optimizes the Pt loading to improve catalytic activity while controlling cost. The Pt nanoparticles are uniformly dispersed without significant agglomeration and form a strong interaction with the CeCuO3 support. Furthermore, this invention broadens the light absorption range and improves photothermal conversion efficiency through the synergistic effect of CeCuO3. The photothermal synergistic effect is significant at 130℃ and 130 mW·cm⁻¹. -2 The methanol conversion rate reaches its peak under light intensity, while the CO selectivity is low. The catalyst in this invention has a stable structure, excellent resistance to carbon deposition and agglomeration, and its activity only decreases by 1.7% after 150 hours of continuous reaction. Its stability is far superior to that of pure support and other comparative catalysts. The preparation process is controllable and reproducible, making it suitable for photothermal catalytic methanol reforming to produce hydrogen and possessing good potential for industrial application. Attached Figure Description
[0018] Figure 1 This is a graph showing the methanol conversion rate at different reaction temperatures in Example 3.
[0019] Figure 2 This is a graph showing the methanol conversion rate under different light intensities in Example 3.
[0020] Figure 3 The graphs show the performance of each embodiment and comparative example under optimal reaction conditions.
[0021] Figure 4 The graphs show the cyclic stability of each embodiment and comparative example. Detailed Implementation
[0022] To enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0023] Example 1 (1% Pt / CeCuO3) 1) Accurately weigh each metal nitrate precursor: 1.7254 g of cerium nitrate hydrate (Ce(NO3)3·6H2O) and 0.9598 g of copper nitrate hydrate (Cu(NO3)2·3H2O), dissolve them in deionized water, and stir until completely dissolved to form a homogeneous metal salt mixed solution. 2) Add 2.5047 g of citric acid (C6H8O7·H2O) to the mixed solution from step 1). Citric acid reacts with metal ions (Ce). 3+ Cu 2+ The molar ratio of the two components was 1.5:1. The mixture was magnetically stirred for 2 hours in a water bath at 60°C until a transparent and uniform sol was formed.
[0024] 3) Remove the beaker containing the sol from step 2) and allow it to stand at room temperature for 20 hours until the sol loses its fluidity and forms a viscous gel. Place it in a drying oven and dry at 90°C for 10 hours to remove moisture and obtain a dry gel. 4) Grind the dried gel from step 3) into powder, place it in a muffle furnace, heat it to 600°C at a heating rate of 3°C / min, calcine for 3 hours, and then cool it naturally to room temperature to obtain CeCuO3 perovskite support powder.
[0025] 5) In step 4), weigh 0.0265 g of chloroplatinic acid (H2PtCl6·6H2O) as a Pt precursor according to a Pt loading of 1% (based on the mass of CeCuO3 support), and dissolve it in deionized water to prepare a Pt precursor solution; add CeCuO3 support powder to the Pt precursor solution, and stir magnetically at room temperature for 5 h to ensure that the Pt precursor is uniformly adsorbed on the support surface; then place it in an oven and dry at 110℃ for 5 h to remove moisture.
[0026] 6) Place the dried sample from step 5) into a tube furnace and heat it to 400°C at a heating rate of 2°C / min. Then, calcine it with an argon-hydrogen mixture for 2-3 hours to decompose and reduce the Pt precursor into Pt nanoparticles and firmly load them onto the CeCuO3 support surface. After calcination, allow it to cool naturally to room temperature and grind it evenly to obtain the target supported catalyst.
[0027] Example 2 (2% Pt / CeCuO3) Compared with Example 1, the mass of chloroplatinic acid in Example 1 was adjusted so that the loading of Pt was 2%, while other conditions remained unchanged.
[0028] Example 3 (3% Pt / CeCuO3) Compared with Example 1, the mass of chloroplatinic acid in Example 1 was adjusted so that the loading of Pt was 3%, while other conditions remained unchanged.
[0029] Example 4 (4% Pt / CeCuO3) Compared with Example 1, the mass of chloroplatinic acid in Example 1 was adjusted so that the loading of Pt was 4%, while other conditions remained unchanged.
[0030] Example 5 (5% Pt / CeCuO3) Compared with Example 1, the mass of chloroplatinic acid in Example 1 was adjusted so that the loading of Pt was 5%, while other conditions remained unchanged.
[0031] Comparative Example 1 (CeCuO3) Compared with Example 1, the mass of chloroplatinic acid in Example 1 was changed to 0g, while other conditions remained unchanged.
[0032] Comparative Example 2 (0.5% Pt / CeCuO3) Compared with Example 1, the mass of chloroplatinic acid in Example 1 was adjusted so that the loading of Pt was 0.5%, while other conditions remained unchanged.
[0033] Comparative Example 3 (6% Pt / CeCuO3) Compared with Example 1, the mass of chloroplatinic acid in Example 1 was adjusted so that the loading of Pt was 6%, while other conditions remained unchanged.
[0034] Comparative Example 4 (3% Pt / CeCoO3) Compared with Example 1, the copper nitrate hydrate in Example 1 was replaced with cobalt nitrate hydrate (Co(NO3)2·6H2O), and the mass of cobalt nitrate hydrate, cerium nitrate hydrate, and chloroplatinic acid was adjusted so that the Pt loading was 3%, while other conditions remained unchanged.
[0035] Comparative Example 5 (3% Pt / LaCuO3) Compared with Example 1, the cerium nitrate hydrate in Example 1 was replaced with lanthanum nitrate hydrate (La(NO3)3·6H2O), and the mass of lanthanum nitrate hydrate, copper nitrate hydrate, and chloroplatinic acid was adjusted so that the Pt loading was 3%, while other conditions remained unchanged.
[0036] like Figure 1As shown, the methanol conversion effect of Example 3 was tested within the temperature range of 90–170℃ after fixing the light intensity. The conversion rate showed a typical pattern of first increasing and then decreasing with temperature. When the temperature increased from 90℃ to 130℃, the heat energy supply of the reaction system continued to increase, the thermal motion of methanol molecules intensified, the activation energy decreased significantly, the oxygen vacancy activity of the CeCuO3 support was fully activated, the catalytic activity of the supported Pt nanoparticles increased simultaneously, the photothermal synergistic effect continued to enhance, and the methanol activation and reforming reaction rates steadily accelerated, thus the conversion rate continued to increase. When the temperature exceeded 130℃ and continued to rise to 150℃ and 170℃, the high temperature caused slight aggregation of Pt nanoparticles, resulting in a reduction in the number of active sites. At the same time, the high temperature intensified side reactions such as methanol cracking, the generated CO covered the active center of the catalyst, and also caused slight lattice distortion of the CeCuO3 support and a decrease in oxygen vacancy concentration, which in turn reduced the photothermal conversion efficiency. Multiple factors together led to a significant decline in the methanol conversion rate.
[0037] To investigate the optimal light intensity, such as Figure 2 The optimal reaction temperature of 130℃ was previously determined, and tests were conducted at 90–170 mW·cm⁻¹. -2 The catalytic performance under varying light intensity also showed an initial increase followed by a slight decrease in conversion rate. The light intensity increased from 90 mW·cm⁻¹. -2 Increased to 130 mW·cm -2 At this time, the catalyst absorbs more light energy, the photothermal conversion efficiency continues to improve, the effective reaction temperature of the system is closer to the optimal value, and the number of photogenerated carriers increases. The photocatalytic effect of CeCuO3 and the thermal catalytic effect of Pt are synergistically enhanced, the methanol molecule is more fully activated, and the conversion rate gradually reaches its peak. When the light intensity exceeds 130 mW·cm -2 Afterwards, excessive light exposure will cause local overheating of the system, resulting in the same side reactions as in the high-temperature section, the problem of active sites being covered, the recombination rate of photogenerated carriers will increase, the quantum efficiency will decrease, and strong light will also slightly oxidize the Pt active sites. Therefore, the methanol conversion rate will only drop slightly.
[0038] Therefore, as Figure 3 As shown, the various embodiments and comparative examples were subjected to temperatures of 130°C and 130 mW·cm⁻¹. -2Tests were conducted under optimal conditions. The conversion rates of all examples were significantly higher than those of the comparative examples, and the conversion rates of Examples 1–5 initially increased and then decreased with increasing Pt loading. When the Pt loading increased from 1% to 3%, the number of active sites continued to increase, the Pt nanoparticles were well dispersed, and the interaction with the CeCuO3 support was continuously enhanced, resulting in a wider light absorption range, improved photothermal conversion efficiency, and continuously optimized methanol activation effect, leading to a steady increase in conversion rate. When the Pt loading exceeded 3% (4%, 5%), excess Pt would aggregate on the support surface, reducing the exposed area of active sites and blocking the light absorption sites of the support, weakening the photothermal synergy, and causing the conversion rate to decrease. Comparative Example 1, pure CeCuO3 without Pt modification, had narrow light absorption, very few active sites, and extremely low conversion rate. Comparative Example 2 (0.5% Pt) had too low a loading, resulting in insufficient modification and limited activity improvement. Comparative Example 3 (6% Pt) showed severe Pt agglomeration, leading to a sharp drop in activity. In Comparative Examples 4 and 5, after replacing the support metal element, the oxygen vacancies in the perovskite were significantly reduced, the catalytic activity of Cu disappeared, and the synergistic effect with Pt failed, resulting in conversion rates far lower than in Example 3. Meanwhile, Example 3 exhibited the lowest CO selectivity because the uniform dispersion of Pt effectively suppressed carbon deposition and side reactions, while the comparative examples showed severe side reactions and higher CO selectivity.
[0039] Figure 4 To test the conversion rate decay under long-term operation, the conversion rates of all samples decreased slightly, but the decay rate of the examples was much lower than that of the comparative examples, with Example 3 showing the best stability. In the examples, the Pt loading was moderate, the nanoparticles were uniformly dispersed and firmly bound to the support, making them less prone to aggregation and loss during the reaction. The CeCuO3 support structure was stable, oxygen vacancies continuously provided activity, and the photothermal synergy accelerated the decomposition of carbon deposits, thus resulting in slow activity decay. In Comparative Example 1, pure CeCuO3 lacked Pt to inhibit carbon deposition, and the active sites were quickly covered and deactivated. In Comparative Examples 2 and 3, due to unreasonable Pt loading, either the modification was insufficient or there was severe aggregation, leading to rapid failure of active sites. In Comparative Examples 4 and 5, the support structure was unstable, prone to lattice collapse, and the activity decay rate was significantly accelerated. Example 3 showed only a 1.7% decay after 150 hours of reaction, thanks to the triple advantages of optimal Pt loading: anti-aggregation, anti-carbon deposition, and structural stability.
[0040] In summary, temperature and light intensity tests clearly defined 130℃ and 130 mW·cm⁻¹ as the optimal values. -2The optimal reaction conditions were determined by the catalyst. Deviations from these conditions resulted in decreased conversion rates due to side reactions and active site agglomeration / oxidation. Component comparison confirmed that 3% Pt loading was the optimal amount; below this value, there were insufficient active sites, and above this value, particle agglomeration occurred, both reducing catalytic efficiency. Stability testing verified that the catalyst exhibited extremely slow activity decay over long-term operation due to its stable structure, resistance to carbon deposition and agglomeration. Overall, this catalyst, through the synergistic effect of reasonable Pt loading and the CeCuO3 support, is perfectly suited for photothermal catalytic methanol reforming to hydrogen production scenarios, exhibiting comprehensive performance far superior to pure support, abnormal Pt loading, and metal-substituted catalysts.
[0041] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to any specific implementation. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A supported perovskite catalyst characterized in that, The catalyst comprises a perovskite-type CeCuO3 support and Pt nanoparticles supported thereon, wherein the Pt loading is 1% to 5% based on the mass of the CeCuO3 support.
2. The supported perovskite catalyst according to claim 1, characterized in that, The load on Pt is 3%.
3. A process for the preparation of the supported perovskite catalyst of claim 1 or 2, characterized in that, Includes the following steps: (1) Weigh out the cerium source and copper source according to the stoichiometric ratio of CeCuO3, dissolve them in deionized water, and stir until completely dissolved; (2) Add citric acid as a complexing agent and stir to dissolve; (3) Heat in a water bath, stir to form a sol, and then age to obtain a gel; (4) Dry the gel to obtain a dry gel; (5) Grind and calcine the dry gel to obtain CeCuO3 perovskite carrier powder; (6) Weigh the Pt precursor according to the target Pt loading, prepare a solution, load the Pt precursor onto the surface of CeCuO3 support by impregnation method, and then dry it; (7) The Pt precursor is reduced to Pt nanoparticles by secondary calcination under a reducing atmosphere, and then cooled and ground to obtain the supported Pt / CeCuO3 catalyst.
4. The preparation method according to claim 3, characterized in that, In step (1), the cerium source is cerium nitrate hydrate, and the copper source is copper nitrate hydrate, with a molar ratio of 1:
1.
5. The preparation method according to claim 3, characterized in that, In step (2), the molar ratio of citric acid to total metal ions is 1.3 to 1.6:1, preferably 1.5:
1.
6. The preparation method according to claim 3, characterized in that, In step (3), the water bath temperature is 60~70℃, the gelation time is 2~3h, and the aging time is 12~24h.
7. The preparation method according to claim 3, characterized in that, In step (5), the calcination heating rate is 2~5℃ / min, the calcination temperature is 550~650℃, and the calcination time is 3~6h.
8. The preparation method according to claim 3, characterized in that, In step (7), the heating rate of the secondary roasting is 1~3℃ / min, the roasting temperature is 350~450℃, and the roasting time is 2~3h; the reducing atmosphere is an argon-hydrogen mixture.
9. The application of a supported perovskite catalyst as described in claim 1 or 2, or a supported perovskite catalyst prepared by the method according to any one of claims 3-8, in the photothermal catalytic methanol steam reforming reaction for hydrogen production.
10. Use according to claim 9, characterized in that, The conditions of the photo-thermal catalytic methanol steam reforming reaction for hydrogen production are: reaction temperature 130℃, light intensity 130 mW·cm -2 .
